SOCIAL SUPPORT AND COPING STRATEGIES AMONG NURSES: A COMPARATIVE STUDY - Ziven Khansa Apta Muamar; Muthia Aryuni; Miranti; Jane Mariem Monepa (Universitas Kadiri, 2026)
Social support and coping strategies are vital components for nurses navigating the various challenges and stressors inherent in their profession. In fact, the level of social support received and the specific coping mechanisms employed significantly influence the overall quality of nursing performance. On that account, this research aimed to evaluate and compare the social support levels and coping strategies used by nurses at Tadulako Hospital and Sis Al Jufri Palu General Hospital. This quantitative study utilized a comparative design with a total sampling technique. The participants included 28 nurses from Tadulako Hospital and 27 nurses from Sis Al Jufri Palu General Hospital. Upon investigation, data analysis conducted via the Mann-Whitney test revealed specific patterns in both facilities. Most nurses at Tadulako Hospital relied on support from significant others. By comparison, those at Sis Al Jufri Palu General Hospital primarily received support from significant others and family members. Regarding coping mechanisms, the majority of nurses at both hospitals utilized problem-focused coping to manage their professional demands. As far as the statistical results are concerned, no significant difference was found in the social support levels between the two groups (p = 0.374). Nevertheless, a significant difference was observed in the specific coping strategies applied by nurses at Tadulako Hospital compared to those at Sis Al Jufri Palu General Hospital (p = 0.033). Ultimately, social support remains an essential factor for healthcare providers, as high levels of support foster the use of adaptive coping strategies necessary to meet the rigors of the job.